Temporal and spatial factors affecting the cross-modal integration of object information - Woods, Andrew Thomas (Trinity College (Dublin, Ireland). School of Psychology, 2005)
This thesis is concerned with how temporal and spatial factors influenced the cross-modal integration of object representations across modalities. Specifically tested was whether temporal synchrony and spatial co-location are crucial for the integration of visual and haptic object information. It was hypothesised that there would be mandatory integration when objects were presented to modalities in temporal synchrony and in the same location in space.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin